2022
DOI: 10.1101/2022.07.19.500688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and biodistribution of Nanoligomers targeting SARS-CoV-2 genome for treatment of COVID-19

Abstract: As the world braces to enter its third year in the coronavirus disease 2019 (COVID-19) pandemic, the need for accessible and effective antiviral therapeutics continues to be felt globally. The recent surge of Omicron variant cases has demonstrated that vaccination and prevention alone cannot quell the spread of highly transmissible variants. A safe and nontoxic therapeutic with an adaptable design to respond to the emergence of new variants is critical for transitioning to treatment of COVID-19 as an endemic d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Penetration of SB_NI_112 across the BBB was confirmed with ICP−MS and detected in the hippocampus (76.1 nM ± 44.3), cortex (49.9 nM ± 11.4), cerebellum, (96.9 nM ± 45.0), and brainstem (96.6 nM ± 32.4) (Figure 2A), which is significantly higher than the dissociation constant of SB_NI_112. 50 Downregulation of NF-κB and NLRP3 with SB_NI_112 leads to dampening of chronic inflammation, while preserving key immune pathways needed to respond to infectious pathogens (63). Despite downregulation of NF-κB and NLRP3, interferon gamma (IFN-γ) expression was significantly higher in prion-infected mice treated with SB_NI_112 (p = 0.048 (two-way t-test, Excel) or p = 0.0468 (one-way ANOVA, Graphpad Prism)) and not significantly different from control NBH mice (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetration of SB_NI_112 across the BBB was confirmed with ICP−MS and detected in the hippocampus (76.1 nM ± 44.3), cortex (49.9 nM ± 11.4), cerebellum, (96.9 nM ± 45.0), and brainstem (96.6 nM ± 32.4) (Figure 2A), which is significantly higher than the dissociation constant of SB_NI_112. 50 Downregulation of NF-κB and NLRP3 with SB_NI_112 leads to dampening of chronic inflammation, while preserving key immune pathways needed to respond to infectious pathogens (63). Despite downregulation of NF-κB and NLRP3, interferon gamma (IFN-γ) expression was significantly higher in prion-infected mice treated with SB_NI_112 (p = 0.048 (two-way t-test, Excel) or p = 0.0468 (one-way ANOVA, Graphpad Prism)) and not significantly different from control NBH mice (Figure 2B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nanoligomers were designed and synthesized (Sachi Bioworks Inc.) according to published methods. 42,43,50,75,76 The nanoligomer is composed of a nanobiohybrid molecule based on antisense peptide nucleic acid (PNA) 42,43,75,77,78 conjugated to nanoparticle 1,2,5 for improved delivery. The PNA moiety was chosen to be 17 bases long (to optimize solubility and specificity) antisense to the start codon regions of nfkb1 (N terminus-C terminus, sequence: AGTGG-TACCGTCTGCTA) and nlrp3 (N terminus-C terminus, sequence: CTTCTACTGCTCACAGG) within the mouse genome (GCF_000001635.27).…”
Section: Downregulation Of Nf-κb and Nlrp3 With Sb_ni_112 Treatment R...mentioning
confidence: 99%
“…Additionally, these methods can also suffer from transport challenges, especially delivery to the brain across the blood-brain barrier, making molecular optimization even more challenging and reducing throughput. By contrast, the Nanoligomer therapeutic platform generates safe, targeted, 34 and highly specific (K D 3.37 nM 35,36 ) RNA-targeting molecules for facile delivery to the brain and other targeted organs and offers both up-and downregulation of desired protein through translational and transcriptional regulation. 37−42 The platform also utilizes an effective bioinformatics approach to identify top molecules for a given target, now allowing high-throughput screening and ranking of different potential targets for a given disease condition, leading to best-in-class and first-in-class therapeutics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nanoligomers utilize peptide nucleic acids (PNAs) as the sequence-specific binding component that demonstrate strong hybridization and specificity to their RNA (or DNA) sequence targets, 43 and exhibit no known enzymatic cleavage, leading to increased stability in human blood serum and mammalian cellular extracts. 44 Given the low K D , 35,36,43 high binding specificity, minimal off-targeting, 35,36 lack of any immunogenic response or accumulation in first pass organs, 34 absence of any observable histological damage to organs even for long (>15− 20 weeks) treatments, [34][35][36]40 and facile delivery to the brain to counter neuroinflammation, 34,37−42 we have demonstrated that Nanoligomers are a safe and targeted approach to screen for therapeutic targets in organoids and rodents for multiple neurodegenerative diseases aboard the International Space Station (ISS). Therefore, not only is the Nanoligomer-based screening well-differentiated from other traditional screening methods on Earth, but the combination of accelerated neuropathology in space and high-throughput screening by the Nanoliogmer platform can also lead to breakthrough therapeutics for different debilitating disease conditions ■ RESULTS AND DISCUSSION High-Throughput In Vitro Screening in Donor-Derived Primary Human Astrocytes.…”
Section: ■ Introductionmentioning
confidence: 99%